Anti-interferon-α antibodies associate with disease activity and prognosis in anti-MDA5-positive dermatomyositis - Chao Sun; Hongxia Yang; Yingfang Zhang; Shiyu Wu; Xinxin Zhang; Wei Jiang; Qinglin Peng; Guochun Wang; Xin Lu (Arthritis Research & Therapy)
Abstract Background Interferons (IFN) are implicated in the pathogenesis of anti-MDA5 dermatomyositis (anti-MDA5-DM), but the presence of anti-IFN antibodies remains unclear. This study aims to assess serum levels of anti-IFN-α antibodies in anti-MDA5-DM patients and explore their clinical associations. Methods Serum samples from 176 anti-MDA5-DM patients and 55 healthy controls were analyzed for anti-IFN-α antibody levels using an in-house ELISA assay, with immunoblot validation in a subset. Associations between anti-IFN-α antibodies and disease activity or prognosis were assessed. Results The prevalence of anti-IFN-α antibodies in anti-MDA5-DM patients was 17.6% (31/176), with higher rates in those aged over 60 years. Anti-IFN-α antibody-positive patients exhibited significantly higher incidences of RP-ILD (67.7% vs. 41.4%, p = 0.008) and pulmonary infections (74.2% vs. 46.2%, p = 0.005), with fungi, particularly Aspergillus, being the predominant pathogens. Serum anti-IFN-α antibody levels positively correlated with IgG (r = 0.48, p < 0.0001), ESR (r = 0.28, p = 0.003), ferritin (r = 0.16, p = 0.03), lung VAS (r = 0.24, p = 0.01), and PhGA VAS (r = 0.28, p = 0.002). Longitudinal analysis showed that changes in anti-IFN-α antibody levels paralleled changes in skin VAS, lung VAS, and PhGA VAS (p = 0.015, 0.005, and 0.004, respectively). Notably, treatment-aggravated cases had increased anti-IFN-α antibody levels from baseline (p = 0.017), while remission cases showed decreased levels (p = 0.004). Mortality was significantly higher in anti-IFN-α positive patients (Log-rank p = 0.006). Conclusion A subset of anti-MDA5-DM patients demonstrated positive serum anti-IFN-α antibodies. The significant association of these antibodies with disease activity and prognosis suggests their potential as a clinical biomarker. Monitoring anti-IFN-α antibody levels may provide an effective means to assess treatment response and predict outcomes in anti-MDA5-DM.